2020
DOI: 10.1101/2020.07.07.191007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection induces germinal center responses with robust stimulation of CD4 T follicular helper cells in rhesus macaques

Abstract: ABSTRACTCD4 T follicular helper (Tfh) cells are important for the generation of long-lasting and specific humoral protection against viral infections. The degree to which SARS-CoV-2 infection generates Tfh cells and stimulates the germinal center response is an important question as we investigate vaccine options for the current pandemic. Here we report that, following infection with SARS-CoV-2, adult rhesus macaques exhibited transient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…We found that SARS-CoV-2-specific CD4+ T cells expressed especially high levels of ICOS, suggesting active helper function of B cells. These findings suggest that SARS-CoV-2-specific cTfh play a key role in effective immunity, and are in line with the observation that the frequency of total cTfh cells increases at the time of SARS-CoV-2 clearance (Thevarajan et al, 2020) and the detection of robust Tfh responses following exposure of rhesus macaques to SARS-CoV-2 (Elzaldi et al, 2020). Interestingly, the SARS-CoV-2-specific cTfh cells we identified exhibit features similar to a population of cTfh shown to be important in the generation of vaccine-induced antibodies against influenza (Bentebibel et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…We found that SARS-CoV-2-specific CD4+ T cells expressed especially high levels of ICOS, suggesting active helper function of B cells. These findings suggest that SARS-CoV-2-specific cTfh play a key role in effective immunity, and are in line with the observation that the frequency of total cTfh cells increases at the time of SARS-CoV-2 clearance (Thevarajan et al, 2020) and the detection of robust Tfh responses following exposure of rhesus macaques to SARS-CoV-2 (Elzaldi et al, 2020). Interestingly, the SARS-CoV-2-specific cTfh cells we identified exhibit features similar to a population of cTfh shown to be important in the generation of vaccine-induced antibodies against influenza (Bentebibel et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…These findings suggest that SARS-CoV-2-specific cTfh cells play a key role in effective immunity and are in line with the observation that the frequency of total cTfh cells increases at the time of SARS-CoV-2 clearance 4 and detection of robust Tfh cell responses following exposure of rhesus macaques to SARS-CoV-2. 36 Interestingly, the SARS-CoV-2-specific cTfh cells we identified exhibit features similar to a population of cTfh cells shown to be important in generation of vaccine-induced antibodies against the flu. 25 Both express high levels of CXCR5 and ICOS.…”
Section: Discussionmentioning
confidence: 65%
“…These results, particularly the presence of individuals with low neutralizing antibodies are interesting as each individual in our cohort has recovered from SARS-CoV-2 infection. This observation suggests that either we missed the period of robust neutralizing antibody production in certain individuals or other mechanisms, such www.nature.com/scientificreports/ as potent SARS-CoV-2 specific T-cell responses [36][37][38][39][40][41][42] , provided effective viral clearance and immunity. Future studies coupling assessment of antibody and T-cell responses with key clinical information (age, sex, severity of symptoms) will be essential to fully understand this complex immune response.…”
Section: Discussionmentioning
confidence: 99%